2006
DOI: 10.1016/j.jeem.2005.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Double dividend hypothesis, golden rule and welfare distribution

Abstract: This paper analyzes the double dividend issues within the framework of overlapping generations models. We characterize the necessary conditions for obtaining a double dividend, i.e. an improvement of environmental and non-environmental welfare when the revenue from the pollution tax is recycled into a change in the labor tax rate.We show that, depending on the initial capital stock and on the intertemporal elasticity of substitution, conditions may be de…ned to simultaneously allow (i) the obtaining of a long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 25 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…By using an overlapping generations model, under the assumption of involuntary unemployment, we examine whether a revenue-neutral increase in the pollution tax compensated by a change of the labor tax can yield a double dividend. This general framework can be related to those of Heijdra (1998), ChiroleuAssouline andFodha (2002) and Bovenberg and van der Ploeg (1996) but differs from them in several ways. Bovenberg and Heijdra (1998) do not explicitly address the double dividend issue but investigate whether a higher pollution tax can be Pareto welfare improving by benefiting all generations.…”
Section: Introductionmentioning
confidence: 91%
“…By using an overlapping generations model, under the assumption of involuntary unemployment, we examine whether a revenue-neutral increase in the pollution tax compensated by a change of the labor tax can yield a double dividend. This general framework can be related to those of Heijdra (1998), ChiroleuAssouline andFodha (2002) and Bovenberg and van der Ploeg (1996) but differs from them in several ways. Bovenberg and Heijdra (1998) do not explicitly address the double dividend issue but investigate whether a higher pollution tax can be Pareto welfare improving by benefiting all generations.…”
Section: Introductionmentioning
confidence: 91%
“…In particular, Goulder [18] and Ligthart [23] showed that the existence of the double dividend essentially depends on the possibility of transferring the global tax burden from the wage earners to some …xed production factors or to other consumers, thus emphasizing the role of heterogeneity. Following in behind this stream of literature, Chiroleu-Assouline and Fodha [9] and [10] studied the existence conditions of a long term double dividend, taking into account the distinction between wage earners and retired consumers, by means of overlapping generations models.…”
Section: Introductionmentioning
confidence: 99%
“…1 In this regard, there are many papers arguing that if the revenue from environmental taxes is used to cut other distortionary taxes (such as labour taxes), it may improve both the environment and social welfare (see, for example, Goulder, 1995;Carraro et al, 1995;Bosquet, 2000;Chiroleu-Assouline and Fodha, 2006). In this sense, environmental regulations may provide a double dividend; this is referred to as "the double dividend hypothesis".…”
Section: Introductionmentioning
confidence: 99%